Synthesis of Conjugated Materials Based on Benzodithiophene - Benzothiadazole and Their Application of Organic Solar Cells - Sylvianti, Nadhila; Kim, Youn Hwan; Kim, Dong Geun; Maduwu, Ratna Dewi; Jin, Ho Cheol; Moon, Doo Kyung; Kim, Joo Hyun (Macromolecular research, 2018)
Electron acceptor-donor-acceptor type oligomers based on benzothiadiazole (BT) unit and a (4,8-bis((2-ethylhexyl)oxy)benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl) bis(trimethylstannane) (BDT) unit have been designed and prepared as electron-donating materials, which are 2,6-[5-(7-methyl-benzo[1,2,5]thiadiazol-4-yl)-thiophen-2-yl]-4,8-bis((2-ethylhexyl)oxy)benzo[1,2-b:4,5-b′]dithiophene) ( BDT-TBT ) and 2,6-[5′-(3′-hexyl-[2,2′]bithiophenyl-5-yl)-7-methyl-benzo[1,2,5]thiadiazole]-4,8-bis((2-ethylhexyl)oxy)benzo[1,2-b:4,5-b′]dithiophene) ( BDT-THTBT ), for Organic Solar Cells (OSCs) with PC 71 BM as electron-accepting materials. The HOMO energy level is elevated by the number of thiophene ring as a p-bridge, which lowers the band gap. Inverted-type organic solar cells (OSCs) with a configuration of ITO/ZnO/ BDT-TBT (or BDT-THTBT ):PC 71 BM/MoO 3 /Al are fabricated. OSC based on BDT-THTBT exhibits the highest power conversion efficiency (PCE) of 1.04% with the best J sc of 4.20 mA/cm 2 .